A Job Recommendation System For Differently Abled Using Neural Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Empowering differently abled is not only a good social cause, but also contributes towards the country’s Gross Domestic Product. This article presents a software application which recommends a job suitable to the differently abled with due consideration to the type and degree of disability. A Neural Networks (NN) model is used to develop the software application. The data set for the same was provided by Enable India, a Non-Government Organisation, involved in empowering the differently abled. The application performed with an accuracy of 87%.